Implementation of Judge Independence in the Process of Implementing Justice in Islamic Law Perspective - Khairul Huda; Bambang Tri Bawono; Achmad Arifullah (Law Development Journal, 2022)
This study aims to analyze and examine the implementation of the independence of judges in the process of administering justice in Indonesia and to understand and examine the implementation of the independence of judges in the administration of justice from an Islamic perspective. This study uses library research methods or library research that is "juridical-normative". The data sources used are secondary data, namely ethical standards as judges with "Islamic character". The data will be analyzed using descriptive analysis method and the theoretical basis used is the principles of qadhi in Islam and the code of ethics for the behavior of Indonesian judges. Based on the data analysis carried out, it is concluded that a judge should maintain his integrity, his honor who has morals and is a mandate from the Most Wise, namely ensuring the establishment of a sense of justice, guaranteeing legal certainty and seeking the benefit of legal values to all Indonesian people.